2001
DOI: 10.1038/88748
|View full text |Cite
|
Sign up to set email alerts
|

Signal transduction through Vav-2 participates in humoral immune responses and B cell maturation

Abstract: B and T lymphocytes develop normally in mice lacking the guanine nucleotide exchange factor Vav-2. However, the immune responses to type II thymus-independent antigen as well as the primary response to thymus-dependent (TD) antigen are defective. Vav-2-deficient mice are also defective in their ability to switch immunoglobulin class, form germinal centers and generate secondary immune responses to TD antigens. Mice lacking both Vav-1 and Vav-2 contain reduced numbers of B lymphocytes and display a maturational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
106
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(113 citation statements)
references
References 38 publications
7
106
0
Order By: Relevance
“…In separate studies, we have shown that at least two components of the BCR signalosome, BTK and PLC-␥2, are required for the activation of NF-B and transcriptional up-regulation of the bcl-x gene (58), 2 further supporting an involvement of the BCR signaling in T2 B cell responses. Like BTK and PLC-␥2, other components of the BCR signalosome including phosphatidylinositol 3-kinase, Vav, and B cell linker protein are involved in the transition of immature B cells to more mature stages (27,28,40,(42)(43)(44)(45). The opposite biological responses of T1 versus T2 and an involvement of the BCR signaling components in this process is also supported by a recent study published during the preparation of this manuscript (65).…”
Section: Discussionsupporting
confidence: 62%
“…In separate studies, we have shown that at least two components of the BCR signalosome, BTK and PLC-␥2, are required for the activation of NF-B and transcriptional up-regulation of the bcl-x gene (58), 2 further supporting an involvement of the BCR signaling in T2 B cell responses. Like BTK and PLC-␥2, other components of the BCR signalosome including phosphatidylinositol 3-kinase, Vav, and B cell linker protein are involved in the transition of immature B cells to more mature stages (27,28,40,(42)(43)(44)(45). The opposite biological responses of T1 versus T2 and an involvement of the BCR signaling components in this process is also supported by a recent study published during the preparation of this manuscript (65).…”
Section: Discussionsupporting
confidence: 62%
“…The block in SLP-76 ⌬2-156 mice could be due to the inability of the SLP-76 mutant to recruit members of the Vav, Itk and͞or Nck families, and͞or additional proteins that may interact with the SLP-76 N-terminal domain (2-4). Neither disruption of individual or dual combinations of the Vav proteins Vav1 and Vav 2 (19)(20)(21)(22), nor of the Tec kinases Itk, Tec, and Rlk͞Txk (23, 24) blocks T cell development at the DN stage.…”
Section: Discussionmentioning
confidence: 99%
“…Animal Use-Ahr and Vav3 knock-out mice have been reported previously (25,38,45 (45,47,48), and Vav3 Ϫ/Ϫ mice and subsequent homogenization in the BL10 genetic background. Unless otherwise stated, 4-month-old mice were used in experiments.…”
Section: Methodsmentioning
confidence: 99%